2009
DOI: 10.1080/01460860903030193
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Support for Parents of Hospitalized Children

Abstract: The findings indicate that parents received a high level of support from nurses. Nurses can promote the quality of family care and should be aware of the importance of the several types of nursing support in meeting the requests of parents. It is important that nurses continue to develop their knowledge about types of communication with the family, especially in providing support for the parent role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
25
4
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 19 publications
6
25
4
1
Order By: Relevance
“…This study also found that according to the mothers, the least and most received nursing support were in the care giving support and parental esteem domains, respectively. In this regard, the findings of Valizadeh and Akbarbegloo [3], Seyedamini [17] and Sanjari et al [18] were in line with this study and indicated that according to the mothers the least and most received nursing support were in the care giving support and parental esteem domains, respectively. Another study by Morsy on two groups of mothers of children hospitalized in the general ward and the intensive care unit showed that the most and least received nursing support in both groups were in the parental esteem and care giving support domains, respectively.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This study also found that according to the mothers, the least and most received nursing support were in the care giving support and parental esteem domains, respectively. In this regard, the findings of Valizadeh and Akbarbegloo [3], Seyedamini [17] and Sanjari et al [18] were in line with this study and indicated that according to the mothers the least and most received nursing support were in the care giving support and parental esteem domains, respectively. Another study by Morsy on two groups of mothers of children hospitalized in the general ward and the intensive care unit showed that the most and least received nursing support in both groups were in the parental esteem and care giving support domains, respectively.…”
Section: Discussionsupporting
confidence: 78%
“…In this regard, Sanjari et.al indicated that there was a significant difference between the mean emotional support and mothers' educational level. Also, there was a significant difference between supportive communication and gender of the newborn [18]. According to the results, it can be concluded that mothers wanted to get the highest amount of support in providing the best care for their newborns, but stated that they needed little emotional support from the nurses.…”
Section: Discussionmentioning
confidence: 87%
“…) and Iran (Sanjari et al . ). The lower perception of Jordanian mothers of nursing support can be explained within two perspectives of the Jordanian healthcare system: nurses' knowledge and perception of the concept of mother's support and workload and shortage of nurses.…”
Section: Discussionmentioning
confidence: 97%
“…In contrast, research at the Iranian Children's Hospital suggests stronger support of nursing personnel expressed by respondents in Iran. Here, the average score was 4.1 points 18 . Analysis of the type and degree of relationship between the two variables monitored (the relationship between mothers'perceptionof stress and staff behavior and perceptions of support provided to mothers by nurses), showed an an indirect linear relationship.…”
Section: Discussionmentioning
confidence: 99%